(untitled) (Bioagro, 2024)
Coffee rust, caused by the biotrophic fungus Hemileia vastatrix Berk & Br., is considered the main disease of the crop. This fungus is widely distributed in coffee-producing localities, causing serious economic damage in all parts of the world. A study of physiological races of H. vastatrix was conducted on 6 isolates collected in the state of Táchira, in Venezuela. Rust monopustules were obtained on ‘Catuai amarillo’ which were later inoculated on ‘Catuai rojo’. Spores obtained from the latter cultivar were then used to inoculate leaf discs of 32 differential clones. After incubation for up to 60 days, visual symptoms were rated using Tamayo scale for disease severity. Results were compared with reported races. Three strains were characterized: race XXXIX (v2, 4, 5, 6, 7, 8, 9, ?) and two pathotypes Hv01ve (v1, 2, 4, 5, 7, 9, ?) and Hv02ve (v1, 2, 4, 5, 6, 7, 9, ?). This is the first report of new races in the country on Coffea Arabica, which shows the evolutive potential of the coffee rust pathogen.